The Effect of Price and Product Quality on Purchasing Decisions for Dharmasan 100 Ml at PT Perusahaan Perdagangan Indonesia - Kusuma Wardani, Denti; Alhassan Musah, Adiza; Nurkhayati, Isnaini (Journal of World Science, 2023)
This research aims to analyze the influence of price and product quality on purchasing decisions for the 100 ml Dharmasan product at PT PPI (Persero) Semarang branch. The data collection method in this research used observation and questionnaires. The sampling technique used purposive sampling of 55 respondents. The independent variables of this research are price and product quality. The dependent variable of this research is purchasing decisions. This study uses a quantitative approach. The analytical methods used are validity test, reliability test, descriptive analysis of respondents, classical assumption test, multiple linear regression method, t-test, F test, and coefficient of determination. Multiple linear regression coefficients were used to analyze the data. Based on calculations using SPSS version 25, the research results show that the regression equation is Y = 0.555 + 0.412X1 + 0.490X2 + e, which can be interpreted as that price (X1) and product quality (X2) have a positive effect on purchasing decisions (Y). Ho was rejected based on the t-test results for price and quality, and Ha was accepted because each variable had a calculated t-value greater than the t-table. The F test results show that Ho is rejected and Ha is accepted because the f-count is greater than the f-table. Based on the analysis of the coefficient of determination, the Adjusted R square value is 0.848, meaning that the price and product quality variables contribute to purchasing decisions by 84.8%. In comparison, the remaining 15.2% is determined by other variables not examined in this research.